Cylindrical conformal array antenna for near field focusing. Issue 6 (8th March 2022) - Li, Yingjun; Yu, Shixing; Kou, Na; Ding, Zhao; Zhang, Zhengping
Abstract: This paper proposes a cylindrical conformal antenna array for near‐field focusing. Two dimensional focusing scanning can be realized by using digital phase shifters. In addition, omnidirectional scanning along circumference of the cylinder can be obtained with good stability by feeding a fixed number of antenna elements in the different section of the cylindrical array. One third of the cylindrical array is fabricated and measured to verify the near‐field focusing performances. Both simulation and measurement show that the proposed cylindrical conformal array antenna can effectively achieve two‐dimensional near‐field focusing scanning. Compared with planar array, cylindrical array can broaden the scanning range to omnidirection with good stability in horizontal dimension. This method can provide references for applications such as radio frequency identification and wireless power transfer.